Gigantic spermatocytic seminoma: A rare tumor of germ cell origin - Prelević Rade; Milev Boško; Milović Novak; Ignjatović Mihajlo; Spasić Aleksandar; Petrović Nikola (Vojnosanitetski Pregled)
Indtorduction. Spermatocytic seminoma represents a rare hystologic type of malignant testicular germ cell tumor with slow course and low malignant potential. Case report. We presented a 69-year-old patient with atypical clinical presentation of spermatocytic seminoma initially diagnosed as gigantic hydrocoellae which compromised walking. After long term evolution clincal picture presented with signs and symptoms of acute scrotum. Preoperative echosonography was performed and the diagnosis of testicular infiltrative tumor was established. After that left scrotal orchiectomy was performed. Patohistological examination revealed spermatocytic seminoma. Conclusion. Inspite good prognosis there is a low probability of development of high grade malignancy sinchronous sarcoma within the testis with a high potential for lymphogenic and hematogenic dissemination. Individual approach is necessary in accordance with the pathohistological diagnosis.